PENGARUH TRICHODERMA TERHADAP PERKECAMBAHAN DAN PERTUMBUHAN BIBIT KAKAO, TOMAT, DAN KEDELAI - Erida Nurahmi; Susanna Susanna; Rina Sriwati (Jurnal Floratek, 2012)
Trichoderma is a free-living fungus, commonly can be found in soil and root ecosystem.  Extensively, it is capable of producing antibiotics, parasite to other fungus, and microorganism that cause diseases on plants.  The objectives of the experiment were to study effects of Trichoderma on germination and growth of cacao, tomato, and soybean. The result showed that provision of Trichoderma (T. harzianum and T. virens) conidia suspension using seed submersion technique did not affect seed germination of cacao, tomato, and soybean, but significantly affected cacao root extension. Provision of Trichoderma through seed submersion on sand box germination gave a positive response to tomato plant, tolerance to cacao plant, and a negative response to soybean plant.  The causing factors of difference responses varied including concentration, application techniques, and kinds of seed.